CHATHUSKA METHODOLOGY: NECTAR OF CHARAKA SAMHITA SUTRASTHANA (AYUSHDHARA, 2021)
Objective: To assess the fundamental concept of Ayurveda explained in Charaka Samhita by the learning methods of Chathushka.Review Methods: Literary review methods were followed throughout the study. Mainly focussed on Charaka Samhita and its Commentaries, Articles related to Chatushka Methodology.Result and Conclusion: Ayurveda is the Upaveda of Atharva Veda and consists of Brihatrayees and Laghutrayess. They have their own textual version that follows a particular style of writing as suited to the subject. The term “Samhita'' denotes complete collection of specific valuable knowledge unavoidable for the improvement of various aspects of life. Since the Vedic literature, the word Samhita is in use. Similarly the main aim of Ayurveda is to protect all aspects of life, so got the name Samhita. Among the Samhitas, Charaka Samhita is divided into eight Sthana and embodiments of knowledge to promote positive health. In Charaka Samhita, Acharya ratified various techniques like Thantrayukti, Vadamarga etc., by adopting a unique methodology known as Chathushka Methodology. Sutra Sthana consists of thirty chapters partitioned into seven quadrants. Each quadrant deals with specific subjects. This paper highlights the influence of Chathushka methodology in identifying the pedagogy of Charaka Samhita to understand the fundamentals of Ayurveda.Data Source: This is a review article and main source of the article is Charaka Samhitha and its commentaries which were available. The main source of Charaka Samhita is the online e - Samhitha of National Institute of Indian Medical Heritage.